The geology and geomorphology of Pulau Jarak, Pulau Sembilan and Pulau Perak - Hussin, Azhar; Abdul Ghani, Azman; Ismail, Khaira; Fauzi, Rosmadi; Richard, Dorall,; S, Gokilan, (Malaysian Journal of Science, 2008)
Pulau Jarak and Pulau Perak in the northern part of the Straits of Malacca constitute the outermost islands of Peninsular Malaysia. Pulau Jarak is a granitic island with a well-developed soil cover on the upper slope which falls straight into the sea with almost no coastal plain. Hence the coastline is dominated by boulders and granitic outcrop. It is fringed by an asymmetrical subsea platform which supports luxuriant coral reef development. Pulau Perak is underlain by a metamorphosed sequence of predominantly thick bedded, low-dipping arenaceous sedimentary rocks which form a broad anticline. Poor soil development is seen in Pulau Perak, being limited to areas of thick guano from ocean birds. Its subaerial morphology of steep precipitous cliffs continue into the sea to a depth of 85 meters. Luxuriant growth of corals and algae plastered the walls of these subsea cliffs.